Tingkat Literasi Keuangan Syariah Mahasiswa Program Studi Ekonomi Syariah dan Perbankan Syariah: Studi Kasus - Elia Mauliana; Cantik Tri Rahajeng (Create: Journal of Islamic Management and Business, 2025)
Financial literacy knowledge is very important to form quality and intelligent students in managing finances. Financial literacy is a life skill that every individual needs to have to support long-term life. Understanding financial literacy helps individuals in planning personal finances and improving their standard of living. Students of the Islamic Economics and Islamic Banking Study Program have received courses related to financial institutions in semesters 6, 7, and 8, so in theory they are expected to have financial literacy skills. This study aims to determine the level of Islamic financial literacy of Islamic Economics and Islamic Banking students. The research method uses a descriptive quantitative approach. The population was 120 people, with a sample of 92 people selected through cluster sampling techniques. Data were analyzed using descriptive statistics. The results showed that the level of Islamic financial literacy of students reached 71.46%. Based on the financial literacy criteria according to Chen and Volpe, this percentage is included in the moderate category. Referring to the OJK classification, the level of financial literacy is included in the sufficient literate category. The average percentage of financial literacy levels in each aspect is: basic sharia financial knowledge of 73.2%, sharia savings and loans of 74.9%, sharia insurance of 68.62%, and sharia investment of 68.9%.